Telematic Music: Performance, Somax2, Co-improvisation, and Pedagogical Aspects - Bomfim, Cássia Carrascoza; Rossetti, Danilo; Malt, Mikhail (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2025.14249, 2025)
Between January 2023 and January 2025, we established the Telematic Music Center at the Faculty of Philosophy, Sciences, and Letters at the University of São Paulo (FFCLRP-USP), Brazil. This center supported the research project Telematic Music: Connectivity in Virtual Environments, funded by the São Paulo Research Foundation (FAPESP), which explored telematic performance through music, audio and video technologies, and artificial intelligence. The project culminated in a remotely produced audiovisual album featuring collaborative works by Cássia Carrascoza and Paulo C. Chagas, along with original compositions by Chagas for flute, live electronics, and video. In partnership with Mikhail Malt, we developed coimprovisations in a virtual space mediated by the AI-driven system Somax2, investigating sound spatialization and immersive audio environments. Simultaneously, we continued the pedagogical work of the Telematic Ensemble LaFlauta at USP. Together with composer Danilo Rossetti, we implemented an educational initiative on telematic chamber music, offering students practical experience with audio technologies and collaborative performance in virtual settings. The ensemble performed works composed specifically for them by Rossetti, Chagas, Iazzetta, and Carrascoza. This article presents key outcomes of the project, emphasizing the artistic collaboration with Malt and Somax2 and the educational impact of telematic ensemble practice.